(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The principal has a strategic role in forming a school climate that supports the strengthening of teacher and student character. This study aims to describe the principal’s leadership style in strengthening character in elementary schools. The method used is qualitative with a case study design. The subjects of the study consisted of principals, grade V teachers, PJOK teachers, and grade V students in several elementary schools in Cimanggung District. Data collection techniques were carried out through interviews, observations, and documentation, with data analysis using the Miles and Huberman model. The results of the study showed that the principal applied a democratic and transformational leadership style, which was reflected through open communication, involvement of school residents in decision-making, and exemplary attitudes. This style is effective in forming teacher character, such as responsibility and integrity, and student character, such as discipline, religiousness, and cooperation. This study concludes that a participatory and value-based leadership style is very relevant to supporting character education in elementary schools.